PARAMETRIC ANALYSIS OF ELECTRICAL ENERGY PRODUCTION BY WIND ENERGY FOR BOZCAADA - Cetin, B.; Alpkaya, M. D. (YILDIZ TECHNICAL UNIV, 2019)
In this study, the economic analysis of the wind power plant to be installed in Bozcaada district has been investigated. The aim of this study is to find the most economical wind turbine for Bozcaada and to analyze the electricity production cost for different economic and technical parameters such as interest rate, wind speed, hub height, capacity factor, etc. As a result, the developed model is solved by using RETScreen and Excel program, and then the effect of the studied parameters on electricity generation cost is investigated. The electricity production cost was found minimum for the Vestas V80-67M turbine. Consequently, Vestas V80-67M was preferred as the most suitable turbine for Bozcaada.
Keywords: Wind Power Plant; Economic Analysis; Electricity Production Cost; RETScreen; POWER-GENERATION; POLICIES; Thermodynamics